Current Community-based Mental Health Promotion Strategies Among children and Adolescents: A Literature Review of Evidence and Feasibility in Indonesia - Sutrimo, Ade; Kusumawardani, Lita Heni (UI Scholars Hub, 2021)
Mental disorders impact people's quality of life globally. A quarter of the world's population consists of children and adolescents who are significantly experiencing mental disorders since the age of 14. Community-based mental health strategies are aimed to overcome the challenges of mental health. The purpose of this review was to explore the evidence of children and adolescents' mental health promotion strategies to be potentially implemented in Indonesia. A literature review design was utilized using PRISMA on 20 journals through Science Direct, Proquest, SAGE, Scopus, EBSCO, and Taylor and Francis, in the last five years, within keywords of community-based, children and adolescents, mental health promotion, strategy. Data were analyzed in a table containing the title, author, year, methodology, results, and recommendations. Several strategies can be implemented to improve mental health in children and adolescents, such as peer group approaches, parental support, and religious education. Community-based mental health promotion strategies can optimize the effective implementation. Rigorous studies on policy evaluation, readiness, pilot studies on the implementation, and other approaches are needed for the more technical implementation of community-based mental health promotion strategies.